Knowledge of Personal Hygiene among Undergraduates - Nurudeen, Akorede Seun Nurudeen; Toyin, Atanda (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Background: Personal hygiene is the act of taking care of oneself, it is also referring to as an act of maintaining the cleanliness of one's body and clothing to improve overall health and well-being. The purpose of the study was to examine if undergraduates know about personal hygiene, investigate if undergraduates of University of Ilorin differ in personal hygiene knowledge based on age, and assess if there is a difference in knowledge of personal hygiene among undergraduates of University of Ilorin based on gender. Methods: A descriptive research design of using surveys was employed for this study. Multi-stage sampling techniques of simple random, proportionate, and convenient sampling techniques were used to select 398 respondents for the study. The researcher developed a questionnaire validated by three experts from the Department of Health Promotion and Environmental Health Education, University of Ilorin was used for the study. ANOVA and Independent t-test was used to test the hypotheses. All hypotheses were tested at 0.05 level of significance. Results: The findings from this study revealed that undergraduates of University of Ilorin know about personal hygiene. The mean values of Yes (330/ 82.9%) is greater than the mean value of No (68/17.8%). There is a significant difference in knowledge of personal hygiene among undergraduates of University of Ilorin based on age (p= 0.023). There is a significant difference in knowledge of personal hygiene among undergraduates of University of Ilorin based on gender (p= 0.018). Conclusion: The study concluded that undergraduates of University of Ilorin know about personal hygiene.